Comparison of Flow Injection MS, NMR, and DNA Sequencing: Methods for Identification and Authentication of Black Cohosh (Actaea racemosa) - Harnly, James (Planta Med, 2015)
Flow injection mass spectrometry and proton nuclear magnetic resonance spectrometry, two metabolic fingerprinting methods, and DNA sequencing were used to identify and authenticate Actaea species. Initially, samples of Actaea racemosa from a single source were distinguished from other Actaea species based on principal component analysis and soft independent modeling of class analogies of flow injection mass spectrometry and proton nuclear magnetic resonance spectrometry metabolic fingerprints. The chemometric results for flow injection mass spectrometry and proton nuclear magnetic resonance spectrometry agreed well and showed similar agreement throughout the study. DNA sequencing using DNA sequence data from two independent gene regions confirmed the metabolic fingerprinting results. Differences were observed between A. racemosa samples from four different sources, although the variance within species was still significantly less than the variance between species. A model based on the combined A. racemosa samples from the four sources consistently permitted distinction between species. Additionally, the combined A. racemosa samples were distinguishable from commercial root samples and from commercial supplements in tablet, capsule, or liquid form. DNA sequencing verified the lack of authenticity of the commercial roots but was unsuccessful in characterizing many of the supplements due to the lack of available DNA.